2015
DOI: 10.1186/s12910-015-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethical problems in intensive care unit admission and discharge decisions: a qualitative study among physicians and nurses in the Netherlands

Abstract: BackgroundThere have been few empirical studies into what non-medical factors influence physicians and nurses when deciding about admission and discharge of ICU patients. Information about the attitudes of healthcare professionals about this process can be used to improve decision-making about resource allocation in intensive care. To provide insight into ethical problems that influence the ICU admission and discharge process, we aimed to identify and explore ethical dilemmas healthcare professionals are faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 36 publications
2
83
1
9
Order By: Relevance
“…In high-pressure intensive care services and beds, deciding whether to discharge a patient who is not quite ready for the general ward to create space for another severely ill patient could be an ethical challenge for a resident. 14 In this study, there was a significant difference between the attitudes of residents in surgical fields and other residents in terms of the necessity of professionalism and ethics education. Surgery "skills-based" residents expressed a lower need for training of ethics than other specialties.…”
Section: Discussionmentioning
confidence: 93%
“…In high-pressure intensive care services and beds, deciding whether to discharge a patient who is not quite ready for the general ward to create space for another severely ill patient could be an ethical challenge for a resident. 14 In this study, there was a significant difference between the attitudes of residents in surgical fields and other residents in terms of the necessity of professionalism and ethics education. Surgery "skills-based" residents expressed a lower need for training of ethics than other specialties.…”
Section: Discussionmentioning
confidence: 93%
“…Commentary Dr. Rose finds herself in a tough situation, perhaps one that many clinicians find equally uncomfortable: a medically unwarranted request from a colleague. Certainly differences in opinion exist among professionals in any field, but, in health care, these differences seem to carry a heavier weight-particularly if the difference in opinion involves a potentially life-threatening diagnosis [1]. In the above case, the difference in opinion is further complicated by the fact that one clinician might be considered experienced in the diagnosis of lower back pain and the other clinician inexperienced.…”
mentioning
confidence: 92%
“…Contemporary studies done in developed countries have consistently demonstrated that nurses working in critical care units as well as other areas face ethical dilemmas concerning issues of patient management [1]. The International Council of Nurses (ICN) Code of Ethics for Nurses has four principal elements that outline the standards of ethical conduct displaying a reflection of the ethical principles governing care in the critical care units.…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of the health problems faced by patients admitted in ICU coupled with extensive use of very sophisticated technology requires at times rapid decision making. These critically ill patients are vulnerable and entirely depend on the caregiver, optimally the nurse working in the critical care unit [1].The nurses working in the critical care areas also have various socio-demographic factors which may affect how they perceive ethical dilemmas and their ethical decision making process.Despite the importance of ethical dilemmas faced by these nurses, little is known about their prevalence, causes, effects and factors affecting their resolution. The existing literature focuses primarily on the problem of nursephysician conflict, and nurse-family conflict, and emphasizes coping mechanisms for nurses rather than improving patient care [11,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation